Editorial for the Special Issue "Antibiotic Prescribing and Antimicrobial Resistance Patterns in Pediatric Patients" - Costanza Vicentini; Carla Maria Zotti (MDPI AG, 2023)
Antibiotic overuse is among the most important factors contributing to the growing problem of antimicrobial resistance (AMR) [...]